Destruction of spin cycloid in (111)c-oriented BiFeO3 thin films by epitaxial constraint : enhanced polarization and release of latent magnetization - Bai, Feiming (2011)
In BiFeO3 films, it has been found that epitaxial constraint results in the destruction of a space